Failed shocks in hypertrophic cardiomyopathy patients: prevalence, predictors and outcome. (19th May 2022) - Segev, A; Fishman, B; Wasserstrum, Y; Beinart, R; Arad, M; Sabbag, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: An implantable cardioverter-defibrillator (ICD) is used in selected high-risk hypertrophic cardiomyopathy (HCM) patients in order to prevent sudden arrhythmic death. The unique features of this population raise concerns regarding the reliability of successful defibrillation. Purpose: To describe the rate and discover potential predictors of failed shocks in HCM patients. Methods: We retrospectively evaluated all HCM patients with an ICD from a single tertiary medical center. Clinical, electrocardiographic and echocardiographic data were collected and compared among patients with and without failed shocks. Results: A total of 99 patients (77% male, 45±17 years old) were analyzed. Over a median follow up of 6.3 years (IQR 2.6-10.7), 20 patients developed sustained ventricular arrhythmia (VTA). Of those, 18 patients received appropriate shocks from their ICD. VTA was associated with younger age at diagnosis, history of syncope and thicker maximal LV width. Six patients experienced at least one failed shock. The likelihood of failed shocks was similar when single or dual coil electrodes were used (dual coils in 67% of patients with failed shocks and 50% in those without), and the only predictor was increased wall thickness [OR 1.2 (1.07-1.38) per 1 mm]. All-cause mortality was low and similar in patients with an without failed shocks (0% vs 8%, P=0.5) Conclusions: Failed shocks are a rare entity in HCM patients. Increased maximal LV width was the only predictor of those events. Our findings support avoiding defibrillation threshold testing routinely, but may indicate its need in patients with extreme LV wall thickening (≥23 mm).